ANTARES upper limits on the multi-TeV neutrino emission from the GRBs detected by IACTs. Issue 3 (29th March 2021) - Albert, A.; André, M.; Anghinolfi, M.; Anton, G.; Ardid, M.; Aubert, J.-J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin, V.; Biagi, S.; et al.
Abstract: The first gamma-ray burst detections by Imaging Atmospheric Cherenkov Telescopes have been recently announced: GRB 190114C, detected by MAGIC, GRB 180720B and GRB 190829A, observed by H.E.S.S. A dedicated search for neutrinos in space and time coincidence with the gamma-ray emission observed by IACTs has been performed using ANTARES data. The search covers both the prompt and afterglow phases, yielding no neutrinos in coincidence with the three GRBs studied. Upper limits on the energetics of the neutrino emission are inferred. The resulting upper limits are several orders of magnitude above the observed gamma-ray emission, and they do not allow to constrain the available models.